Efektivitas Pemungutan Retribusi Tempat Rekreasi dan Olahraga sebagai Upaya Peningkatan Pendapatan Asli Daerah Kabupaten Bogor (Studi Kasus di Badan Pengelolaan Pendapatan Daerah) Tahun 2018 - Windi Damaryanti; selvi selvi (Jurnal Ilmu Administrasi Publik, 2021)
The purpose of this study is to analyze the effectiveness of retribution  collection on recreational and sports sites and analyze the obstacles as well as the efforts made to overcome these obstacles. This study used a qualitative approach with observation and interview techniques with the Head of Planning and Development Sub-Division (Bappenda), the Head of Tourism Attraction Section (Disbudpar), academics and retribution payer. From the results of the research effectiveness in 2018 is quite effective. The contribution of effectiveness in 2015-2018 did not contribute to the original income of Bogor Regency. Obstacle from this collection is only at one tourist attraction, the quality of tourism development is still low and there is lack of community knowledge. Efforts to overcome these obstacles are exploring the potential of other attractions, structuring and developing the potential of other attractions and increasing tourism promotion. Suggestions for this research are to increase the cooperation of officers and increase the number of supervisors.